Birth order and relationship quality between adult children and parents - Antti O. Tanskanen (Finnish Yearbook of Population Research, 2020)
The neglected middleborn hypothesis predicts that middleborn children should have a worse relationship quality with their parents compared to firstborn and lastborn children. However, prior studies investigating this question have produced mixed results. In this study, the neglected middleborn hypothesis was tested using a large-scale, population-based sample of younger adults from Germany. Relationship quality was measured by contact frequency, emotional closeness, intimacy and amount of conflict participants reported towards their mothers and their fathers. It was found that middleborns reported less intimacy towards their mothers than lastborns. However, in all other cases, middleborns did not differ from firstborns or lastborns in their relationship quality with their mothers and fathers. Thus, the study did not find convincing support for the neglected middleborn effect.